PENYULUHAN DAN KEBERDAYAAN PETANI KARET POLA SWADAYA DI KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Arif Budiman Fa’atdillah; Roza Yulida; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose ofthisresearchare: (1) Assess the role ofan extension ofrubber farmingactivities. (2) Analyzingthe level ofempowermentrubber farmers. (3) Analyze theachievement of the objectivesof theextension asseen frombetterfarming, better business, andbetterliving. This research was conductedinTanjungBeluduVillage and Simpang KotaMedan Village ofKelayang Sub-District inIndragiriHulu District, samplingmethodused ispurposivesamplingmethodwith atotal sample of120farmers. Hallcounselingconductedagricultural extensionfisheryandforestryKelayang sub-districtbeenquite instrumentalin runninga rolethat includesdissemination, consultancy, supervision. However, there aresomeroles thathave not been implementedproperlyandneed to be improvedrole,such aseducation, facilitation, monitoringandevaluationarestill consideredlessa role. Non-pattern rubberfarmerempowermentDistrict ofKelayangcategorizedquite helpless. Empowermentis viewedfrom the aspect ofempowerment ofhuman resources is still consideredless powerful. Meanwhileproductive economicand institutionalaspectsconsidereddefenseless. Achievement of the objectivesof extensioncategorizedquiteachieved.Achievement of the objectivesof extensionseen fromthe betterfarmingandbetterlivingthat has been categorizedreached.whiletheachievement of the objectivesof extensionseen from thebetter businessstillconsideredlessachieved.   Keywords :The Role, Empowerment, Farmers, Rubber.